Plant-Derived Cell-Free Biofactories for the Production of Secondary Metabolites - Buntru, Matthias; Hahnengress, Nils; Croon, Alexander; Schillberg, Stefan (Frontiers in Plant Science, 2022)
Cell-free expression systems enable the production of proteins and metabolites within a few hours or days. Removing the cellular context while maintaining the protein biosynthesis apparatus provides an open system that allows metabolic pathways to be installed and optimized by expressing different numbers and combinations of enzymes. This facilitates the synthesis of secondary metabolites that are difficult to produce in cell-based systems because they are toxic to the host cell or immediately converted into downstream products. Recently, we developed a cell-free lysate derived from tobacco BY-2 cell suspension cultures for the production of recombinant proteins. This system is remarkably productive, achieving yields of up to 3 mg/mL in a one-pot in vitro transcription–translation reaction as well as highly active energy and cofactor regeneration pathways. Here, we demonstrate for the first time that the BY-2 cell-free lysate also allows the efficient production of several classes of secondary metabolites. As case studies, we synthesized lycopene, indigoidine, betanin and betaxanthins, which are useful in the food, cosmetic, textile and pharmaceutical industries. Production was achieved by the co-expression of up to three metabolic enzymes. For all four products, we achieved medium to high yields. However, the yield of betanin (555 µg/mL) was outstanding, exceeding the level reported in yeast cells by a factor of more than 30. Our results show that the BY-2 cell-free lysate is suitable not only for the verification and optimization of metabolic pathways, but also for the efficient production of small to medium quantities of secondary metabolites.